﻿The role of pharmacists' interventions in improving drug-related problems, blood pressure, and quality of life of patients with stage 5 chronic kidney disease - Peri; Azizah Nasution; Alwi Thamrin Nasution (Pensoft Publishers, 2022)
This six-month cohort study analyzed the impact of pharmacy interventions (PI) on drug-related problems (DRPs), blood pressure (BP), and quality of life (QoL) among patients with stage 5 chronic kidney disease (CKD) (n = 83) admitted to Pirngadi Hospital, Medan, Indonesia period February to July 2021. DRPs, BP, and QoL of the patients were analyzed before and after PI. DRPs were analyzed applying PCNE version 9, BP scores were extracted from the patients' medical records. Their QoL was assessed using a WHOQoL questionnaire. The impacts of PI on the incidence of DRPs, BP, and the patients' QoL were analyzed applying Wilcoxon Signed Rank and Friedman test in the SPSS program version 23.0. The number of DRPs was significantly reduced from 470 before PI to 162 following PI (p = 0.000). The patients' QoL improved significantly from 40 ± 9.87 before PI to 69 ± 12. 45 after PI, p = 0.000. PI is crucial to improve the outcomes of CKD patients.